Systematics of Brucepattersonius Hershkovitz, 1998 (Rodentia, Sigmodontinae): molecular species delimitation and morphological analyses suggest an overestimation in species diversity. Issue 6 (18th August 2021) - Abreu, Edson Fiedler; Jung, Diego Marques Henriques; Christoff, Alexandre Uarth; Valiati, Victor Hugo; Jansa, Sharon A.; Percequillo, Alexandre Reis
Abstract : The genus Brucepattersonius currently includes eight valid species from the Atlantic Forest of south-eastern Brazil and north-eastern Argentina. Most of those species were described in the past 20 years, based on very small sample sizes: four species are known only from their type localities. Concerns on the taxonomic validity of some Brucepattersonius species have been raised in the recent literature. In this study, we present a phylogenetic hypothesis including samples throughout the distribution of the genus (among them the holotypes of two species) and employed single-locus molecular species delimitation analyses to provide a new hypothesis for species limits within Brucepattersonius . We also analysed intra- and interpopulation morphological and morphometric variation to apply an integrative taxonomic approach to species delimitation. Our phylogenetic inference of molecular data recovered four strongly supported clades within Brucepattersonius, which were recognized as distinct operational taxonomic units in all species delimitation analyses. The first two clades represent the Caparaó mountain range endemic B. griserufescens and its sister-group, the recently described species B. nebulosus . The third clade comprises several specimens assigned to B. soricinus but also includes the holotype of B. igniventris ; we revise these species limits accordingly. The last clade is composed of samples from southern Brazil assigned to B. iheringi . Based on morphological and morphometric analyses, we find no clear structure among the three described species from Misiones Province, Argentina ( B. guarani, B. misionensis and B. paradisus ) and B. inheringi from southern Brazil, suggesting that those samples represent a single species. Therefore, in the present study we propose that the genus Brucepattersonius comprises only four diagnosable species: B. griserufescens (including B. albinasus ), B. nebulosus, B. soricinus (including B. igniventris ) and B. iheringi (including B. guarani, B. misionensis and B. paradisus ).